Hyperdominance in fruit production in the Brazilian Atlantic rain forest: the functional role of plants in sustaining frugivores. (16th August 2016) - Staggemeier, Vanessa G.; Cazetta, Eliana; Morellato, Leonor Patrícia Cerdeira
Abstract: The availability of fruits is critical for tropical forests, where the majority of plant species rely upon animal vectors for seed dispersal. However, we do not know how fruit production is temporally distributed over species and families. Two plant families are particularly important in floristic inventories of Atlantic rain forests: Arecaceae, a few species of which are highly abundant; and Myrtaceae, which is abundant and displays outstanding species diversity. In this context, we asked whether hyperdominance occurs in fruit production in the Atlantic rain forest, and whether it occurs in the abundant species of Arecaceae and Myrtaceae. We investigated whether the temporal fruit production patterns differ between Myrtaceae, Arecaceae, and the plant community as a whole. We also applied a functional dispersion index to assess the temporal fruit diversity over a 2‐yr period, with regard to morphological and phenological traits. We found that the phenomenon of hyperdominance occurs in fruit production: five species accounted for more than half of the pulp biomass. Arecaceae fruit biomass peaked at the end of wet season, overlapping with the community peak; whereas Myrtaceae species fruited throughout the year and were an important resource during periods of food scarcity. Myrtaceae filled more of the fruit morphospace over time because their fruits exhibit a large range of morphologies and phenological strategies. Our results demonstrated the importance of combining phenology and fruit morphology in the evaluation of resource availability, which revealed periods of high fruit diversity that could support a range of frugivore sizes and maintain overall ecosystem functionality.